Analysis of Service Quality Satisfaction of E-KTP Service at Public Administration and Civil Registration Office of Bogor District - Rizq, Shafira; Djamaludin, Moh Djemdjem; Nurhadryani, Yani (Journal of Consumer Sciences, 2018)
The purpose of this study was to analyze the satisfaction of service quality in the E-KTP service of the Bogor District Population and Civil Registration Service. The design of this study was a cross-sectional study at Disdukcapil Bogor District. The method used in this study is Servqual, importance performance analysis (IPA), and customer satisfaction index (CSI) with 100 respondents selected using a convenience technique. The result of customer satisfaction index analysis shows that the community has been "quite satisfied" with a value of 61%, and is more inclined towards dissatisfaction. This is in accordance with the results of satisfaction using Servqual analysis (service quality), Disdukcapil's performance has not been able to meet the expectations of the community in almost all indicators, except the indicator "costs to be incurred". The indicator has a positive value, but is still small and close to zero, which is only 0.01. The results of importance performance analysis (IPA) indicate that there is a need to improve the indicators of ease of handling requirements, speed of service processes and facilities and physical condition of service office buildings.